Fostering Students’ Vocabulary Mastery through Anagram Word Games - Nabila, Elda; Suharsih, Siti; Hakim, Rahman (Journal of English Language Teaching and Cultural Studies, 2025)
Learning basic English requires a strong command of vocabulary.  Junior high school students are expected to have a basic command of English vocabulary.  However, many junior high students still lack sufficient vocabulary. The purpose of this study was to see if the anagram word game was successful in improving vocabulary knowledge among seventh-grade students during the academic year 2024-2025. This study employed a quantitative approach with a quasi-experimental, non-equivalent control group design.  The experimental group was class 7D, and the control group was class 7E, both of which included 35 pupils.  This study employed a basic random sampling approach. The instrument of this research was a test. It consisted of 15 questions in multiple-choice form for the pre-test and the post-test. The researcher prepared a worksheet as well. After the data was collected, the data analysis was done through the normality test, homogeneity test, and independent samples T-test. The results showed that the data were normally distributed and homogeneous. Moreover, the independent sample T-test sig. (2- tailed) was 0.029, which was lower than alpha 0.05. It showed that the anagram word game is effective for students’ vocabulary mastery in the seventh grade.